Preliminary inventory of atmospheric emissions (SO2, NOx and TSP) from different industrial sectors in Costa Rica - Alfaro-Alfaro, Daniel (2021)
The use of fuels, urbanization growth, and economic development have influenced the generation of atmospheric pollutants such as NOx (nitrogen oxides), SO2 (sulfur dioxide), and TSPs (Total Suspended Particles). The Costa Rican industrial sector has different category companies such as glass melting and manufacturing of food products and clothing, which release emissions of these pollutants into the atmosphere. The main objective of this research is to generate a preliminary inventory of atmospheric emissions (NOx, SO2, and TSP) from different industrial sectors in Costa Rica. The inventory was conducted in 2019 and included samplings and measurements of pollutants from chimneys of different production processes (companies) from 2014 and 2015.  The sampling and the corresponding measurement of pollutant concentrations (NOx, SO2 and TSP) were conducted using Testo 350 to measure NOx and SO2 and an APEX portable particle counter to quantify TSPs. Data was tabulated using Microsoft Excel, while graphics were generated using R programming language in the R studio interface. The industrial sector entitled “manufacturing of food products” presents the highest amounts of pollutants, with values equal to 1246.14 tons/year, 1959.54 tons/year and 651.01 tons/year for NOx, SO2, and TSP, respectively, for 2014; and 2,622.14 tons/year, 3,257.64 tons/year and 346.40 tons/year, respectively, for 2015.